2023
DOI: 10.1021/acsptsci.3c00088
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Ghrelin(1–8) Analogues with Improved Stability and Functional Activity for PET Imaging

Abstract: The highest affinity ghrelin-based analogue for fluorine-18 positron emission tomography, [Inp1,Dpr3(6-FN),1Nal4,Thr8]ghrelin(1–8) amide (1), has remarkable subnanomolar receptor affinity (IC50 = 0.11 nM) toward the growth hormone secretagogue receptor 1a (GHSR). However, initial in vivo PET imaging and biodistribution of [18F]1 in mice demonstrated an unfavorable pharmacokinetic profile with rapid clearance and accumulation in liver and intestinal tissue, prompting concerns about the metabolic stability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…17 The manuscript by Wu et al describes PET probes for tryptophan metabolism mediated by indoleamine-2,3-dioxygenase 1 (IDO1). L-and D-enantiomers of 4-fluoro-and 6-fluoro-5-methoxytryptophan were radiolabeled via 18 F/ 19 F exchange. In vivo PET imaging of L-[ 18 F]16 (Figure 2) and ex vivo biodistribution studies in tumor-bearing mice showed prominent tumor uptake and high contrast.…”
Section: Imaging and Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…17 The manuscript by Wu et al describes PET probes for tryptophan metabolism mediated by indoleamine-2,3-dioxygenase 1 (IDO1). L-and D-enantiomers of 4-fluoro-and 6-fluoro-5-methoxytryptophan were radiolabeled via 18 F/ 19 F exchange. In vivo PET imaging of L-[ 18 F]16 (Figure 2) and ex vivo biodistribution studies in tumor-bearing mice showed prominent tumor uptake and high contrast.…”
Section: Imaging and Therapymentioning
confidence: 99%
“…A focused library was synthesized and evaluated in a structure−activity−stability relationship study to further understand the structural importance of the chemical functions in the context of stability and receptor affinity. 19 The manuscript by Domling et al describes the design, synthesis, and preliminary biological evaluation by autoradiography of fluorine-18 PET radiopharmaceuticals for PD1/PD-L1 imaging. 20 The manuscript by Stadlbauer et al describes six 64 Culabeled PD-L1 radiotracers.…”
Section: Imaging and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A focused library was synthesized and evaluated in a structure−activity−stability relationship study to further understand the structural importance of the chemical functions in the context of stability and receptor affinity. 19 The manuscript by Domling et al describes the design, synthesis, and preliminary biological evaluation by autoradiography of fluorine-18 PET radiopharmaceuticals for PD1/PD-L1 imaging. 20 The manuscript by Stadlbauer et al describes six 64 Culabeled PD-L1 radiotracers.…”
Section: Imaging and Therapymentioning
confidence: 99%
“…As a result, ghrelin analogues that were developed as imaging agents have been noted as having poor in vitro stability in human serum, with structural modifications required in order to improve stability. 21,22 One important modification is replacing the acyl connection on Ser 3 with an amide linkage, to prevent ester hydrolysis. 4 However, studies have demonstrated that when ghrelin binds to its receptor, part of its peptide structure folds into an α-helical conformation approximately from Pro 7 to Gln 14 .…”
Section: Introductionmentioning
confidence: 99%